The association between self-control and satisfaction in life among Filipino older adults - Laarni Caorong (Jurnal Ners, 2022)
Introduction: Self-control has been associated with a host of positive life outcomes. This correlational study was aimed at determining the link between self-control and life satisfaction among the older population. Methods: This study used a quantitative correlational design. Ninety-six (96) older adult residents of Iligan City and Lanao del Norte, Mindanao Philippines, who met the inclusion criteria were recruited. This quantitative study made use of two standardized instruments namely the Brief Self-Control Scale (BSCS) and the Satisfaction with Life Scale (SWLS). The association was assessed using Pearson correlation statistics. Results: There is a significant relationship between the older adults’ self-control and their life satisfaction. The computed r value is 0.248 (p < 0.05). Evidently, there is a positive relationship between self-control and life satisfaction. This current study has provided evidence to support the assumption that exercising self-control leads to life satisfaction. Conclusions: As a significant positive relationship between the older adults’ self-control exercise and their life satisfaction was proven, this means that effective exercise of self-control positively leads to better life outcomes such as satisfaction in life.  Linking self-control exercise with life satisfaction offers an innovative way for us to know why some people may feel more satisfied with life than others.